Analisis Term Ightarafa Ghurfatan Biyadihi dalam Q.S. Al-Baqarah (2) Ayat 249 dan Relevansinya dengan Hiponatremia - M Muhtaram Syarif; Raden Kurnia Kholiska (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
This article discusses the term ightarafa ghurfatan biyadihi on QS. Al-Baqarah (2): 249 and its relevance to hyponatremia. This reading is intended to give an understanding to the story of Thalut and Jalut in the Qur'an because each story certainly has wisdom. Then the method used for analysis is the maudhu'i and tahlili methods. This study concludes two things that are the answer to the formulation of the problem, namely: First, the scholars' interpretations agree with the term ightarafa ghurfatan biyadihi, interpreting Thalut's command to his troops to drink water with only their hands. Second, the relevance of the verse to hyponatremia is that everyone who drinks water excessively at one time will cause bad symptoms in the health of the body.